the development of women's movement in libya society between empowerment and activation : a documentation study - سليمان محمود العبيدي , د. أمال (Dirasat in Economics and Business, 2004)
'fhe Historical Background of .b ,a provides some understa- ~di~g of the factors and elements hich have shaped the develop- w ' . . . ent of women s position m ~byan society. Each historical era has played a crucial role in affecting the women's movement in Libya. Therefore, this paper seeks to explore the development of the women's movement in Llbya through five main stages: first, the Ottoman period 1551- 1911; second, the Italian occu pation 1911-194 3; third, the British and French administra tions 1943-1951; fourth, the mo narchical period 19 51-1969. Finally, from the finding of the revolution in September 1969 to date. The fmdings of the study showed that the practical and widely-publicised official policies of the Libyan regime since 1969 towards women were aimed at encouraging women to play a significant role in social, political and economic changes within Libyan society. However, the reality in Libyan society corresp onds to the male position. Women lack authority and par ticipate less, so have less capacity to activate the decision making process within the society.